2021
DOI: 10.1186/s41824-021-00109-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined amino acid PET-MRI for identifying recurrence in post-treatment gliomas: together we grow

Abstract: Purpose The aim of this study is to compare the diagnostic accuracy of amino acid PET, MR perfusion and diffusion as stand-alone modalities and in combination in identifying recurrence in post-treatment gliomas and to qualitatively assess spatial concordance between the three modalities using simultaneous PET-MR acquisition. Methods A retrospective review of 48 cases of post-treatment gliomas who underwent simultaneous PET-MRI using C11 methionine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Comprehensive imaging-based diagnosis is the most practical and most commonly applied method although primarily imaging-based determination cannot exclude the possibility that a small number of living tumor cells are present in or around the lesion. When the viable tumor is mixed with RN, an overlap of diffusion restriction can occur [ 2 , 13 , 14 , 35 , 41 , 45 ], particularly in cases with infiltrative pathology (e.g., glioma), and may have possibly resulted in a difference in the bevacizumab response in RN, which shows a diffusion-restriction pattern. The limitation that the pathology of the corresponding lesions were not analyzed in the present study, this should be taken into consideration when interpreting the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive imaging-based diagnosis is the most practical and most commonly applied method although primarily imaging-based determination cannot exclude the possibility that a small number of living tumor cells are present in or around the lesion. When the viable tumor is mixed with RN, an overlap of diffusion restriction can occur [ 2 , 13 , 14 , 35 , 41 , 45 ], particularly in cases with infiltrative pathology (e.g., glioma), and may have possibly resulted in a difference in the bevacizumab response in RN, which shows a diffusion-restriction pattern. The limitation that the pathology of the corresponding lesions were not analyzed in the present study, this should be taken into consideration when interpreting the results.…”
Section: Discussionmentioning
confidence: 99%
“…4 6 10 18 Previous studies have revealed that overexpression of VEGF in resected RN lesions and the degree of radiation injury are correlated with the amount of VEGF expression. 14 29 Since preventing VEGF from reaching its capillary targets is a logical treatment strategy for RN, bevacizumab, a humanized monoclonal antibody against VEGF, might be an effective treatment option. 11 28 Gonzalez et al…”
Section: Introductionmentioning
confidence: 99%
“…Compared with PET/CT, it has an increased soft tissue contrast and lacks of ionizing radiation exposure, which outperforms PET/CT in many applications [ 156 ] . It has been used in both neurodegenerative disorders [ 157 – 159 ] and glioma [ 160 162 ] , with above-mentioned radiotracers, PET/MRI has achieved much better results than using PET or MRI individually, and also PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…18 Comparative studies in high-grade glioma (HGG) using amino acid PET radiotracers in parallel comparison with MRI found high sensitivity but limited specificity for contrast-enhanced MRI in TR detection of HGG, although the sensitivity was low in low-grade glioma. 23,24 For that reason, we decided to include contrast-enhanced low-grade glioma on preoperative MRI. In fact, one of these patients had a recurrence with histology of HGG.…”
Section: Discussionmentioning
confidence: 99%